CLADISTIC ANALYSIS OF A PROBLEMATIC AMMONITE GROUP: THE HAMITIDAE (CRETACEOUS, ALBIAN-TURONIAN) AND PROPOSALS FOR NEW CLADISTIC TERMS - Monks N. (My University, 2002)
The Hamitidae are a family of mid-Cretaceous heteromorph ammonites including lineages leading to four other families. Problems are outlined in trying to describe the phylogeny of completely extinct groups such as these heteromorph ammonites using the existing cladistic terminology, which is largely concerned with extant taxa and their ancestors. To solve these problems, two new terms are proposed: †crown groups and †stem groups, which are equivalent to crown and stem groups in terms of the evolutionary history of a clade, but are not defined on the basis of extant taxa. Instead they are defined by the topology of the phylogenetic tree, the †crown group being a clade defined by synapomorphies but which gave rise to no descendants. A †stem group is a branch of a phylogenetic tree which comprises the immediate sister groups of a given †crown group but is not itself a clade. Examples of these terms are described here with reference to the phylogeny of the Hamitidae and their descendants. The Hamitidae are paraphyletic and form †stem groups to a number of †crown groups, namely the Anisoceratidae, Baculitidae, Scaphitidae, and Turrilitidae. The definitions of the genera and subgenera are refined with respect to the type species and the clades within which they occur, and four new genera are described: Eohamites, Helicohamites, Sziveshamites, and Planohamites.
Keywords: CRETACEOUS; AMMONOIDEA; HETEROMORPH AMMONITES; HAMITIDAE; PHYLOGENY; CLADISTICS; Mesozoic::Cretaceous; Мезозой::Меловая